IMPLEMENTASI MANAJEMEN KELAS DALAM MENINGKATKAN EFEKTIVITAS PROSES PEMBELAJARAN DI MTS YAPDI - Zaubi, Madar; Sembiring, Ari Wibowo; Harahap, Fitra Amalia; Azzahrah, Nindya; Halawa, Syafitri (LPPM Universitas Bina Bangsa, 2025)
The implementation of effective classroom management is the key to creating a conducive learning environment and achieving educational goals optimally. This study aims to analyze the implementation of classroom management at MTs Yapdi in improving the effectiveness of the learning process. The method used is qualitative with a descriptive qualitative approach. This study also includes a literature study by utilizing existing sources such as scientific articles and books related to this study. The results of the study indicate that classroom management at MTs Yapdi has been implemented well, including systematic planning, implementation, and evaluation. The main supporting factors are teacher commitment, adequate facilities, and cooperation between schools and parents